Infrageneric classification of Elwendia (Apiaceae) with a restored species - Kljuykov, Eugene V.; Zakharova, Ekaterina A.; Degtjareva, Galina V.; Samigullin, Tahir H. (Phytotaxa, 2023)
Elwendia is a middle-sized genus with its center of diversity in Central Asia. Due to the progress in recent molecular phylogenetic studies, the genus has been restored and expanded by the inclusion of eastern species of Bunium. However, it still lacks a modern infrageneric classification system based on integrative analyses of molecular, morphological, and karyological evidence. Here, we present the most comprehensive phylogenetic analysis of the genus to date, covering all species within the genus. We used DNA sequences from the nuclear ribosomal internal and external transcribed spacers and sampled 21 morphological characters for each species. As a result, an infrageneric classification system of Elwendia is proposed with 6 sections and 11 subsections. Diagnostically important morphological characters include specializations of fruits and stem leaves. Of particular interest is the congruence between molecular and chromosomal data. Descriptions and species composition of the sections and subsections are provided. Elwendia longiloba is resurrected from the synonymy of E. hissarica.